Designing Ar-Fhat Bakery Toast Packaging Using The Quality Function Deployment (QFD) Method - Nur Ihwan Safutra; A. Dwi Wahyuni P (PT. SAFARI AMALIA, 2022)
The determining factor for the success of a product lies with the consumer, therefore a design that is strictly adapted to the needs and desires of the consumer is needed. In a situation of intense competition, in order to increase sales volumes and market mastery, it is increasingly realized the need for a marketing strategy that is not only based on the needs of consumers, but also competitors who target the same target consumers , by therefore, companies need to anticipate various opportunities and obstacles in the marketing process. Packaging products with an elegant and unique look from competing products will provide their own selling value to the products produced. If done correctly, the company will understand consumer needs and translate them into product designs that are not only effective but also have a good image in the eyes of consumers. From the results of the analysis using the method QFD on Ar-Fath Bakery can it is known the packaging material to be used, the variety of models, the length of the packaging, the width of the packaging and also the height of the packaging where for the main material , namely ivory paper and for printing design drawings using digital printing materials. For the mo del variation used is an attractive and safe packaging design during delivery by adding full attributes to the packaging of Ar Fhat Bakery toast. For the length of the packaging using a size of 20 cm, the width of the packaging is 10 cm and the height of the packaging uses a size of 6 cm.